Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

Isotope metrics refine herbivory among three nominally herbivorous reef fishes of socio-ecological importance - Joshua Pi; Stephane Martinez; Dana T. Cook; Milo Tasopulu; John Rulmal; Michelle J. Paddack; Nicole L. Crane; Giacomo Bernardi; Jonathan D. Cybulski; Kelton W. McMahon (Coral Reefs, 2026)
Herbivorous coral reef fishes are often assigned to different functional groups based on feeding mode and presumed ecosystem processes, such as algal removal ( i.e. , functional herbivory). However, these functional assignments do not necessarily identify assimilated resources nor predict nutritional pathways supporting fish biomass. We used stable carbon and nitrogen isotopes of amino acids to refine our understanding of herbivory among three nominally herbivorous fishes: Chlorurus spilurus , Ctenochaetus striatus , and Naso lituratus . Amino acid carbon isotope fingerprinting indicated much higher and more variable algal carbon contribution for N. lituratus (52.0% [22.0–84.1]) than C. spilurus (5.4% [0.9–17.8]) or C. striatus (4.8% [0.8–15.6]), which were corroborated by low trophic transfer values of N. lituratus ( Δδ 15 N Glu-Lys = 6.0 ± 0.9‰), high source δ 15 N Lys values (4.7 ± 1.0‰), and low microbial reworking ΣV values (0.9 ± 0.2). Conversely, higher Δδ 15 N Glu-Lys values of C. spilurus (7.9 ± 0.9‰) and C. striatus (9.0 ± 1.1‰) coupled with low δ 15 N Lys values (3.6 ± 1.0‰; 3.6 ± 1.1‰, respectively) and higher ΣV values (1.4 ± 0.2; 1.3 ± 0.2, respectively) indicated increased reliance on heterotrophically recycled production ( e.g. , bacteria, detritus, sponge tissue, mucus). Taken together, these data indicate N. lituratus as the most algivorous among our study species, while its broad source credible intervals may reflect epibiont assimilation, algal source variability, or intraspecific dietary variation. By linking carbon source assimilation and trophic transfer at the molecular level, we show that functionally “herbivorous” fishes can occupy distinct nutritional niches and that nutritional and functional definitions of herbivory may not always align.

Skipped spawning in a protandric hermaphrodite: Elucidating the physiological mechanisms in common snook Centropomus undecimalis using reproductive biology and energetics - Alexis A. Trotter; Jared L. Ritch; Jessica L. Carroll; Kristin L. Cook; Gregory V. Onorato; Kristen W. Rynerson; David O. Westmark; Colin P. Shea (Journal of Fish Biology, 2026)
Recent acoustic telemetry research has demonstrated that a portion of the common snook Centropomus undecimalis population in Florida skips annual spawning; however, the details of why some individuals skip spawning are unclear. We conducted a comprehensive study of C. undecimalis reproductive biology to determine if a certain population demographic (e.g. size, age, sex, biological condition) skips spawning in a representative estuary in Florida (Tampa Bay). Reproductive parameters, specifically histological examination of ovaries and testes, analysis of reproductive hormone levels and estimates of energetics including fish condition, hepatosomatic and mesenteric fat indices, were analysed for 254 females and 210 males over two consecutive spawning seasons (2016 and 2017). The results agreed with the known reproductive biology of the species and provided a more comprehensive description of developmental patterns throughout the spawning season. Fish that skipped spawning, defined here as an individual of reproductively mature size having both undeveloped gonads and undetectable levels of primary hormone (17β‐estradiol in females, 11‐ketotestosterone in males), represented 18% of fish sampled. Skip spawning individuals were collected from both estuarine and riverine sites, and were predominately smaller and younger females that had spawned at least once previously as females. Fish that skipped spawning had a lower body condition, a lower fat index and, in particular, a lower liver index. As skipped spawning was predominately observed in younger and smaller female C. undecimalis that were energetically depleted, we suggest that the combination of sex transition from male to female, followed by participation in spawning in the next season, leads to most instances of skipped spawning for the species.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Detection of foodborne viruses in berries – State of science and future considerations - Lee-Ann Jaykus; Sabah Bidawid; Albert Bosch; Sophie Butot; Nigel Cook; Sanjay Gummalla; James Lowther; Neda Nasheri; Rosa M. Pintó; Donald W. Schaffner; Magnus Simonsson; Branko Velebit; et al. (Food Control, 2026)

An Expansion of Weight Inclusivity to Include Body Autonomy and Harm Reduction: Striving for Health Equity - Rachel W. Goode; Tyisha Harper-Cooks; Ana Paola Campos; Katherine Matthes; Julian Robles; Claudia M. Calderon; Michelle Chen Lee; Millicent N. Robinson; Ramine C. Alexander (Journal of the Academy of Nutrition and Dietetics, 2026)

Wavelet analysis of concentric crater fill surface ridges - Claire W. Cook; Shane Byrne (Icarus, 2026)

Sequence stratigraphy and relative sea level variations in Kaštela Bay, Dalmatian coast, Croatia, and implications for the submerged palaeolandscapes and archaeology of the late Pleistocene, marine isotope stage 3 and marine isotope stage 2 - Simon Fitch; Slavica Bosnjak; Jessica W. Cook Hale; Vedran Barbarić; Timothy A. Shaw; Tanghua Li (Quaternary Science Reviews, 2025)

Surplus nutrient exports differ between irrigated and high-rainfall agricultural catchments: a tale of two catchments in South East Australia - Robert Sargent; Wei Wen Wong; Andrew W. Western; Perran Cook; Anna Lintern (Journal of Hydrology, 2025)

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Annotated checklist of Australian fossil non-marine aquatic molluscs - Winston F. Ponder; Alex G. Cook; Sherri Donaldson; Michael W. Klunzinger (Molluscan Research, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Rewetting alongside biochar and sulphate addition mitigates greenhouse gas emissions and retain carbon in degraded upland peatlands - Peduruhewa H. Jeewani; Robert W. Brown; Chris D. Evans; Jack Cook; Benjamin P. Roberts; Mariecia D. Fraser; David R. Chadwick; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Correlations between catchment-scale farm infrastructure densities and stocking rate to stream nutrient concentrations in dairy-dominant catchments - Jonah Lee Bas; Andrew W. Western; Robert Sargent; Wei Wen Wong; Perran Cook; Anna Lintern (Journal of Environmental Management, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Seasonal trends in marine heatwaves highlight vulnerable coastal ecoregions and historic change points in New Zealand - Shinae Montie; François Thoral; Robert O. Smith; Felix Cook; Leigh W. Tait; Matthew H. Pinkerton; David R. Schiel; Mads S. Thomsen (New Zealand Journal of Marine and Freshwater Research, 2024)
Marine heatwaves (MHWs) have increased worldwide in intensity, frequency, and duration, often with severe impacts on ecologically and socio‐economically important coastal habitats. Most MHW studies have focused on summer events in specific regions or global open‐water analyses with little consideration to seasonality or spatial biogeography of the nearshore zone. We address this research gap by analysing changes to MHWs across seasons and ecoregions, within 12 nautical miles (NM) of New Zealand's coastline, an area with high biodiversity and endemism. We used season‐specific linear trend analysis with temporal breakpoints between 1982 and 2021 to identify the number of MHW events and MHW days, and mean, maximum, and cumulative intensity of MHWs for New Zealand coastal ecoregions. Across ecoregions, 69.5% of 200 trend analyses increased significantly whereas the remaining 30.5% were unaffected. For the significant increases, temporal breakpoints occurred between 1994 and 2012. We conclude that MHWs have become stronger, longer and more frequent across coastal New Zealand, but with some variability within and between regions. Our trend‐analyses could enable retrospective analyses of biological tipping‐points and inform management practices that may enhance the resilience of ecoregions yet to face MHW breakpoints or those in the initial stages of major climatic changes.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Behavioural responses of Sandwich terns following the construction of offshore wind farms - Chris B. Thaxter; Ros M. W. Green; Mark P. Collier; Rachel C. Taylor; Robert P. Middelveld; Emily S. Scragg; Lucy J. Wright; Aonghais S. C. P. Cook; Ruben C. Fijn (Marine Biology, 2024)

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Lights, Cameras, Stream: Dietetic Interns' Experiences with Live Virtual Nutrition Education and Food Demonstration Program for Older Adults - W. Bignell; A. Cook; A. Cobble (Journal of the Academy of Nutrition and Dietetics, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Estimation of individual stem volume and diameter from segmented UAV laser scanning datasets in Pinus taeda L. plantations - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2023)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Penelope K. Lindeque; Isabelle Hann; Helen E. Parry; Kathryn B. Cook; Anthony J. W. Lindley; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis , accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus- dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Ethnicity, socioeconomic status, income inequality, and colorectal cancer outcomes: evidence from the 4C2 collaboration - Cathy J. Bradley; Amy Anderson-Mellies; Evelinn A. Borrayo; Jennifer Anne Doherty; Omar A. Escontrías; David O. Garcia; Shiraz I. Mishra; Andrew L. Sussman; Cynthia A. Thomson; David W. Wetter; Linda S. Cook (Cancer Causes & Control, 2022)

Prioritization and thresholds for managing biological invasions in urban ecosystems - L. J. Potgieter; M. F. J. Aronson; A. J. Brandt; C. N. Cook; M. Gaertner; N. E. Mandrak; D. M. Richardson; N. Shrestha; M. W. Cadotte (Urban Ecosystems, 2022)

Culture Variabilities of Human iPSC-Derived Cerebral Organoids Are a Major Issue for the Modelling of Phenotypes Observed in Alzheimer’s Disease - Damián Hernández; Louise A. Rooney; Maciej Daniszewski; Lerna Gulluyan; Helena H. Liang; Anthony L. Cook; Alex W. Hewitt; Alice Pébay (Stem Cell Reviews and Reports, 2022)

Effect of varied unmanned aerial vehicle laser scanning pulse density on accurately quantifying forest structure - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2022)

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Megadroughts and pluvials in southwest Australia: 1350–2017 CE - Alison J. O’Donnell; W. Lachlan McCaw; Edward R. Cook; Pauline F. Grierson (Climate Dynamics, 2021)
Declining winter rainfall coupled with recent prolonged drought poses significant risks to water resources and agriculture across southern Australia. While rainfall declines over recent decades are largely consistent with modelled climate change scenarios, particularly for southwest Australia, the significance of these declines is yet to be assessed within the context of long-term hydroclimatic variability. Here, we present a new 668-year (1350–2017 CE) tree-ring reconstruction of autumn–winter rainfall over inland southwest Australia. This record reveals that a recent decline in rainfall over inland southwest Australia (since 2000 CE) is not unusual in terms of either magnitude or duration relative to rainfall variability over the last seven centuries. Drought periods of greater magnitude and duration than those in the instrumental record occurred prior to 1900 CE, including two ‘megadroughts’ of > 30 years duration in the eighteenth and nineteenth centuries. By contrast, the wettest > decadal periods of the last seven centuries occurred after 1900 CE, making the twentieth century the wettest of the last seven centuries. We conclude that the instrumental rainfall record (since ~ 1900 CE) does not capture the full scale of natural hydroclimatic variability for inland southwest Australia and that the risk of prolonged droughts in the region is likely much higher than currently estimated.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Use of Drift Studies to Understand Seasonal Variability in Sea Turtle Stranding Patterns in Mississippi - Melissa Cook; Jaymie L. Reneker; Redwood W. Nero; Brian A. Stacy; David S. Hanisko; Zhankun Wang (Frontiers in Marine Science, 2021)
Stranded sea turtles provide valuable information about causes of mortality that threatens these imperiled species. Many potential factors determine whether drifting sea turtles are deposited on shore, discovered by people, and reported to stranding networks resulting in successful documentation. We deployed 182 sea turtle cadavers and 115 wooden effigy drifters with affixed GPS-satellite tags to study stranding probability in the northern Gulf of Mexico (nGOM) in an effort to better understand seasonal stranding variations in this region. Public reports of beached carcasses were recorded to determine reporting rates. Season and distance from shore greatly influenced beaching results. During winter months when strandings are infrequent and sea turtle abundance is likely low in cold nearshore waters, carcasses had an 80–90% probability of beaching. Beaching probability was reduced to 37–50% during the spring, which is the period of greatest strandings in this region. During summer months when relatively few strandings are documented, the probability of a carcass beaching dropped to only 4–8%. Low summer stranding rates were coincident with higher rates of decomposition (7%) attributed to warmer water temperatures, more frequent scavenging (69% of carcasses), and shifting wind and current patterns which drive carcasses offshore or to remote locations. As waters cooled in the fall, probability of carcasses beaching increased to 40–48%, coincident with a small pulse in strandings that often occurs during this period. Only 28% of carcasses and effigies came ashore on mainland beaches and were easily available for discovery by the public, 49% were on barrier islands that are publicly accessible and 23% beached in dense salt marshes where discovery would be unlikely. The 47% of objects that did not beach included those lost at sea and carcasses that were likely scavenged or decomposed. Only 22% of beached carcasses were reported due to infrequent (11%) reporting on barrier islands. Notably, only 50% of carcasses deposited on mainland beaches were reported, which was lower than anticipated. We recommend additional efforts to increase reporting rates of carcasses by the public and use of dedicated surveys to detect stranded sea turtles, especially on barrier islands in this region.

Immersion challenge of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. did not increase the severity of Neoparamoeba perurans ‐induced amoebic gill disease (AGD) - Chloe J. English; Natasha A. Botwright; Mark B. Adams; Andrew C. Barnes; James W. Wynne; Paula C. Lima; Mathew T. Cook (Journal of Fish Diseases, 2021)
Amoebic gill disease (AGD) is one of the main health issues impacting farmed Atlantic salmon. Neoparamoeba perurans causes AGD; however, a diversity of other amoeba species colonizes the gills and there is little understanding of whether they are commensal or potentially involved in different stages of gill disease development. Here, we conduct in vivo challenges of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. to investigate their pathogenicity to Atlantic salmon gills. Additionally, we assessed whether the presence of Nolandella sp. and Pseudoparamoeba sp. influences the onset and/or severity of N. perurans ‐induced AGD. All three strains attached and multiplied on the gills according to qPCR analysis. Furthermore, minor gross gill lesions and histological changes were observed post‐exposure. While N. perurans was found associated with classical AGD lesions, Nolandella sp. and Pseudoparamoeba sp. were not found associated with lesion sites and these lesions did not meet the expected composite of histopathological changes for AGD. Moreover, the presence of these non‐ N. perurans species did not significantly increase the severity of AGD. This trial provides evidence that cultured Nolandella sp. and Pseudoparamoeba sp. do not induce AGD and do not influence the severity of AGD during the early stages of development.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Large climate mitigation potential from adding trees to agricultural lands - Melissa Chapman; Wayne S. Walker; Susan C. Cook‐Patton; Peter W. Ellis; Mary Farina; Bronson W. Griscom; Alessandro Baccini (Global Change Biology, 2020)
While improved management of agricultural landscapes is promoted as a promising natural climate solution, available estimates of the mitigation potential are based on coarse assessments of both agricultural extent and aboveground carbon density. Here we combine 30 meter resolution global maps of aboveground woody carbon, tree cover, and cropland extent, as well as a 1 km resolution map of global pasture land, to estimate the current and potential carbon storage of trees in nonforested portions of agricultural lands. We find that global croplands currently store 3.07 Pg of carbon (C) in aboveground woody biomass (i.e., trees) and pasture lands account for an additional 3.86 Pg C across a combined 3.76 billion ha. We then estimate the climate mitigation potential of multiple scenarios of integration and avoided loss of trees in crop and pasture lands based on region‐specific biomass distributions. We evaluate our findings in the context of nationally determined contributions and find that the majority of potential carbon storage from integration and avoided loss of trees in crop and pasture lands is in countries that do not identify agroforestry as a climate mitigation technique.

Development of an instrumented thoracoscopic surgical trainer for objective evaluation of esophageal atresia/tracheoesophageal fistula repair - Ashton A. Moorhead; David Nair; Chris Morison; Nicholas J. Cook; Spencer W. Beasley; Jonathan M. Wells (Medical & Biological Engineering & Computing, 2020)

Case–control study of endogenous sex steroid hormones and risk of endometrial cancer - Christine M. Friedenreich; Jeroen W. G. Derksen; Thomas Speidel; Darren R. Brenner; Emily Heer; Kerry S. Courneya; Linda S. Cook (Cancer Causes & Control, 2020)

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Climate Change Vulnerability of American Lobster Fishing Communities in Atlantic Canada - Blair J. W. Greenan; Nancy L. Shackell; Kiyomi Ferguson; Philip Greyson; Andrew Cogswell; David Brickman; Zeliang Wang; Adam Cook; Catherine E. Brennan; Vincent S. Saba (Frontiers in Marine Science, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Analysis of recombinant inbred line populations derived from wheat landraces to identify new genes for wheat stem sawfly resistance - Andrea C. Varella; David K. Weaver; Nancy K. Blake; Megan L. Hofland; Hwa-Young Heo; Jason P. Cook; Peggy F. Lamb; Katherine W. Jordan; Eduard Akhunov; Shiaoman Chao; Luther E. Talbert (Theoretical and Applied Genetics, 2019)

3D Printing of Metformin HCl PVA Tablets by Fused Deposition Modeling: Drug Loading, Tablet Design, and Dissolution Studies - Mariam Ibrahim; Morgan Barnes; Robert McMillin; Daniel W. Cook; Sarah Smith; Mathew Halquist; Dayanjan Wijesinghe; Thomas D. Roper (AAPS PharmSciTech, 2019)

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Effects of group size on school structure and behaviour in yellow‐eyed mullet Aldrichetta forsteri - K. L. Middlemiss; D. G. Cook; A. R. Jerrett; W. Davison (Journal of Fish Biology, 2018)
Schooling behaviour in yellow‐eyed mullet Aldrichetta forsteri , a common fish species in New Zealand estuarine habitats, was investigated to identify interaction rules associated with group formation. Tank‐based three‐dimensional studies of three group sizes (15, 75 and 150 individuals) were carried out to measure the effects of these different group sizes on school structure during control, predation risk and foraging behavioural states. Increased group size positively correlated with nearest‐neighbour distance in control and foraging states. Swimming speed was the lowest in all three behavioural states in groups of 15 fish compared with 75 or 150. Immediate behavioural response following visual exposure to a simulated avian predator differed between groups resulting in loss of structure in larger groups. School shape was an oblong–oblate spheroid with a length, breadth and height ratio of 5:2:1 and the area of free space surrounding individual fish was spherical in shape with a high degree of spatial isotropy present in all size groups. These findings challenge traditional theories based on either local or global properties as key drivers of group structure. Instead, our results suggest that a more collaborative approach involving both group size and rules pertaining to nearest‐neighbour interactions affects collective behaviours in this species.

Coagulase-negative staphylococci are associated to the mild inflammatory pattern of healthcare-associated meningitis: a retrospective study - S. Couffin; D. Lobo; F. Cook; P. H. Jost; V. Bitot; R. Birnbaum; B. Nebbad; B. Aït-Mamar; W. Lahiani; M. Martin; G. Dhonneur; R. Mounier (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Can seasonal dynamics of allelochemicals play a role in plant invasions? A case study with Helianthus tuberosus L. - Rita Filep; Robert W. Pal; Viktória L. Balázs; Mátyás Mayer; David U. Nagy; Bradley J. Cook; Ágnes Farkas (Plant Ecology, 2016)

Rapid identification of bovine MHCI haplotypes in genetically divergent cattle populations using next-generation sequencing - Deepali Vasoya; Andy Law; Paolo Motta; Mingyan Yu; Adrian Muwonge; Elizabeth Cook; Xiaoying Li; Karen Bryson; Amanda MacCallam; Tatjana Sitt; Philip Toye; Barend Bronsvoort; et al. (Immunogenetics, 2016)

Participant understanding and recall of informed consent for induced pluripotent stem cell biobanking - Tristan McCaughey; Christine Y. Chen; Elisabeth De Smit; Gwyneth Rees; Eva Fenwick; Lisa S. Kearns; David A. Mackey; Casimir MacGregor; Megan Munsie; Anthony L. Cook; Alice Pébay; Alex W. Hewitt (Cell and Tissue Banking, 2016)

Identifying the physical features of marina infrastructure associated with the presence of non-native species in the UK - Victoria Foster; Rebecca J. Giesler; A. Meriwether W. Wilson; Christopher R. Nall; Elizabeth J. Cook (Marine Biology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Dimethylsulfoniopropionate (DMSP) Increases Survival of Larval Sablefish, Anoplopoma fimbria - Jonathan S. F. Lee; Rachel S. Poretsky; Matthew A. Cook; Jose J. Reyes-Tomassini; Barry A. Berejikian; Frederick W. Goetz (Journal of Chemical Ecology, 2016)

Use of an allostatic neurotechnology by adolescents with postural orthostatic tachycardia syndrome (POTS) is associated with improvements in heart rate variability and changes in temporal lobe electrical activity - John E. Fortunato; Catherine L. Tegeler; Lee Gerdes; Sung W. Lee; Nicholas M. Pajewski; Meghan E. Franco; Jared F. Cook; Hossam A. Shaltout; Charles H. Tegeler (Experimental Brain Research, 2016)

Estimating the eruptive volume of a large pyroclastic body: the Otowi Member of the Bandelier Tuff, Valles caldera, New Mexico - Geoffrey W. Cook; John A. Wolff; Stephen Self (Bulletin of Volcanology, 2016)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

A tree-ring field reconstruction of Fennoscandian summer hydroclimate variability for the last millennium - Kristina Seftigen; Jesper Björklund; Edward R. Cook; Hans W. Linderholm (Climate Dynamics, 2015)

Reconstruction of the springtime East Asian Subtropical Jet and Western Pacific pattern from a millennial-length Taiwanese tree-ring chronology - W. E. Wright; B. T. Guan; Y.-H. Tseng; E. R. Cook; K.-Y. Wei; S.-T. Chang (Climate Dynamics, 2015)

Identifying hot spots of security vulnerability associated with climate change in Africa - Joshua W. Busby; Kerry H. Cook; Edward K. Vizy; Todd G. Smith; Mesfin Bekalo (Climatic Change, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Efficiency and robustness of ant colony transportation networks - Zoe Cook; Daniel W. Franks; Elva J. H. Robinson (Behavioral Ecology and Sociobiology, 2014)

The invertebrate communities associated with a Chrysanthemum coronarium-invaded coastal sage scrub area in Southern California - Roy W. Cook; Theresa Sinicrope Talley (Biological Invasions, 2014)

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Sigma factors in a thousand E . coli genomes - Helen Cook; David W. Ussery (Environmental Microbiology, 2013)
Summary Everyone working with bacterial genomics is familiar with the phrase ‘too much data’. In this G enome U pdate, we discuss two methods for helping to deal with this explosion of genomic information. First, we introduce the concept of calculating a quality score for each sequenced genome, and second, we describe a method to quickly sort through genomes for a particular set of protein families. We apply these two methods to all of the current E scherichia coli genomes available in the T he N ational C enter for B iotechnology I nformation database. Out of the 2074 E . coli / S higella genomes listed ( J une, 2013), only less than half (983) are of sufficient quality to use in comparative genomic work. Unfortunately, even some of the ‘complete’ E . coli genomes are in pieces, and a few ‘draft’ genomes are good quality. Six of the seven known sigma factors in E . coli strain K ‐12 are extremely well conserved; the iron‐regulating sigma factor FecI (σ 19 ) is missing in most genomes. Surprisingly, the E . coli strain CFT073 genome does not encode a functional RpoD (σ 70 ), which is obviously essential, and this is likely due to poor genome assembly/annotation. We find a possible novel sigma factor present in more than a hundred E . coli genomes.

Achieving Conservation Science that Bridges the Knowledge–Action Boundary - CARLY N. COOK; MICHAEL B. MASCIA; MARK W. SCHWARTZ; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
There are many barriers to using science to inform conservation policy and practice. Conservation scientists wishing to produce management‐relevant science must balance this goal with the imperative of demonstrating novelty and rigor in their science. Decision makers seeking to make evidence‐based decisions must balance a desire for knowledge with the need to act despite uncertainty. Generating science that will effectively inform management decisions requires that the production of information (the components of knowledge) be salient (relevant and timely), credible (authoritative, believable, and trusted), and legitimate (developed via a process that considers the values and perspectives of all relevant actors) in the eyes of both researchers and decision makers. We perceive 3 key challenges for those hoping to generate conservation science that achieves all 3 of these information characteristics. First, scientific and management audiences can have contrasting perceptions about the salience of research. Second, the pursuit of scientific credibility can come at the cost of salience and legitimacy in the eyes of decision makers, and, third, different actors can have conflicting views about what constitutes legitimate information. We highlight 4 institutional frameworks that can facilitate science that will inform management: boundary organizations (environmental organizations that span the boundary between science and management), research scientists embedded in resource management agencies, formal links between decision makers and scientists at research‐focused institutions, and training programs for conservation professionals. Although these are not the only approaches to generating boundary‐spanning science, nor are they mutually exclusive, they provide mechanisms for promoting communication, translation, and mediation across the knowledge–action boundary. We believe that despite the challenges, conservation science should strive to be a boundary science, which both advances scientific understanding and contributes to decision making. Logrando que la Ciencia de la Conservación Trasponga la Frontera Conocimiento‐Acción

Greater impulsivity is associated with decreased brain activation in obese women during a delay discounting task - Luke E. Stoeckel; Donna L. Murdaugh; James E. Cox; Edwin W. Cook; Rosalyn E. Weller (Brain Imaging and Behavior, 2013)

Rejoinder: challenge and opportunity in the study of ungulate migration amid environmental change - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)

Animal migration amid shifting patterns of phenology and predation: lessons from a Yellowstone elk herd - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)
Migration is a striking behavioral strategy by which many animals enhance resource acquisition while reducing predation risk. Historically, the demographic benefits of such movements made migration common, but in many taxa the phenomenon is considered globally threatened. Here we describe a long‐term decline in the productivity of elk ( Cervus elaphus ) that migrate through intact wilderness areas to protected summer ranges inside Yellowstone National Park, USA. We attribute this decline to a long‐term reduction in the demographic benefits that ungulates typically gain from migration. Among migratory elk, we observed a 21‐year, 70% reduction in recruitment and a 4‐year, 19% depression in their pregnancy rate largely caused by infrequent reproduction of females that were young or lactating. In contrast, among resident elk, we have recently observed increasing recruitment and a high rate of pregnancy. Landscape‐level changes in habitat quality and predation appear to be responsible for the declining productivity of Yellowstone migrants. From 1989 to 2009, migratory elk experienced an increasing rate and shorter duration of green‐up coincident with warmer spring–summer temperatures and reduced spring precipitation, also consistent with observations of an unusually severe drought in the region. Migrants are also now exposed to four times as many grizzly bears ( Ursus arctos ) and wolves ( Canis lupus ) as resident elk. Both of these restored predators consume migratory elk calves at high rates in the Yellowstone wilderness but are maintained at low densities via lethal management and human disturbance in the year‐round habitats of resident elk. Our findings suggest that large‐carnivore recovery and drought, operating simultaneously along an elevation gradient, have disproportionately influenced the demography of migratory elk. Many migratory animals travel large geographic distances between their seasonal ranges. Changes in land use and climate that disparately influence such seasonal ranges may alter the ecological basis of migratory behavior, representing an important challenge for, and a powerful lens into, the ecology and conservation of migratory taxa.

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

A high-throughput SNP marker system for parental polymorphism screening, and diversity analysis in common bean (Phaseolus vulgaris L.) - Matthew W. Blair; Andrés J. Cortés; R. Varma Penmetsa; Andrew Farmer; Noelia Carrasquilla-Garcia; Doug R. Cook (Theoretical and Applied Genetics, 2013)

Summary Workshop Report: Facilitating Oral Product Development and Reducing Regulatory Burden Through Novel Approaches to Assess Bioavailability/Bioequivalence - James E. Polli; Jack A. Cook; Barbara M. Davit; Paul A. Dickinson; Domenick Argenti; Nancy Barbour; Alfredo García-Arieta; Jean-Marie Geoffroy; Kerry Hartauer; Shoufeng Li; Amitava Mitra; Francis X. Muller; et al. (The AAPS Journal, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Transient Supplementation of Anabolic Growth Factors Rapidly Stimulates Matrix Synthesis in Engineered Cartilage - Kenneth W. Ng; Christopher J. O’Conor; Lindsay E. Kugler; James L. Cook; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Prioritising biosecurity investment between agricultural and environmental systems - David C. Cook; Rob W. Fraser; Jeffrey K. Waage; Matthew B. Thomas (Journal of Consumer Protection and Food Safety, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Characterization of zinc transport by divalent metal transporters of the ZIP family from the model legume Medicago truncatula - Brian W. Stephens; Douglas R. Cook; Michael A. Grusak (BioMetals, 2011)

Conducting Drug Abuse Investigations in Natural Environments: Potential Directions for Medical Toxicology Research - Edward W. Boyer; Richard J. Fay; Aaron Cook; Martin Buckosh; Patricia L. Hibberd; Patricia Case (Journal of Medical Toxicology, 2010)

Increased belowground biomass and soil CO 2 fluxes after a decade of carbon dioxide enrichment in a warm‐temperate forest - Robert B. Jackson; Charles W. Cook; Jeffrey S. Pippen; Sheila M. Palmer (Ecology, 2009)
Atmospheric CO 2 concentrations have risen 40% since the start of the industrial revolution. Beginning in 1996, the Duke Free‐Air CO 2 Enrichment experiment has exposed plots in a loblolly pine forest to an additional 200 μL/L CO 2 compared to trees growing in ambient CO 2 . This paper presents new belowground data and a synthesis of results through 2008, including root biomass and nutrient concentrations, soil respiration rates, soil pore‐space CO 2 concentrations, and soil‐solution chemistry to 2 m depth. On average in elevated CO 2 , fine‐root biomass in the top 15 cm of soil increased by 24%, or 59 g/m 2 (26 g/m 2 C). Coarse‐root biomass sampled in 2008 was twice as great in elevated CO 2 and suggests a storage of ~20 g C·m −2 ·yr −1 . Root C and N concentrations were unchanged, suggesting greater belowground plant demand for N in high CO 2 . Soil respiration was significantly higher by 23% on average as assessed by instantaneous infrared gas analysis and 24‐h integrated estimates. N fertilization decreased soil respiration and fine‐root biomass by ~10–20% in both ambient and elevated CO 2 . In recent years, increases in root biomass and soil respiration grew stronger, averaging ~30% at high CO 2 . Peak changes for root biomass, soil respiration, and other variables typically occurred in midsummer and diminished in winter. Soil CO 2 concentrations between 15 and 100 cm depths increased 36–60% in elevated CO 2 . Differences from 30 cm depth and below were still increasing after 10 years' exposure to elevated CO 2 , with soil CO 2 concentrations >10 000 μL/L higher at 70‐ and 100‐cm depths, potentially influencing soil acidity and rates of weathering. Soil solution Ca 2+ and total base cation concentrations were 140% and 176% greater, respectively, in elevated CO 2 at 200 cm depth. Similar increases were observed for soil‐solution conductivity and alkalinity at 200 cm in elevated CO 2 . Overall, the effect of elevated CO 2 belowground shows no sign of diminishing after more than a decade of CO 2 enrichment.

Phylogenetic endemism: a new approach for identifying geographical concentrations of evolutionary history - DAN ROSAUER; SHAWN W. LAFFAN; MICHAEL D. CRISP; STEPHEN C. DONNELLAN; LYN G. COOK (Molecular Ecology, 2009)
We present a new, broadly applicable measure of the spatial restriction of phylogenetic diversity, termed phylogenetic endemism (PE). PE combines the widely used phylogenetic diversity and weighted endemism measures to identify areas where substantial components of phylogenetic diversity are restricted. Such areas are likely to be of considerable importance for conservation. PE has a number of desirable properties not combined in previous approaches. It assesses endemism consistently, independent of taxonomic status or level, and independent of previously defined political or biological regions. The results can be directly compared between areas because they are based on equivalent spatial units. PE builds on previous phylogenetic analyses of endemism, but provides a more general solution for mapping endemism of lineages. We illustrate the broad applicability of PE using examples of Australian organisms having contrasting life histories: pea‐flowered shrubs of the genus Daviesia (Fabaceae) and the Australian species of the Australo‐Papuan tree frog radiation within the family Hylidae.

Accountability, Reporting, or Management Improvement? Development of a State of the Parks Assessment System in New South Wales, Australia - Marc Hockings; Carly N. Cook; R. W. Carter; Robyn James (Environmental Management, 2009)

Transcriptome Analyses of Amoebic Gill Disease-affected Atlantic Salmon (Salmo salar) Tissues Reveal Localized Host Gene Suppression - James W. Wynne; Maree G. O’Sullivan; Mathew T. Cook; Glenn Stone; Barbara F. Nowak; David R. Lovell; Nicholas G. Elliott (Marine Biotechnology, 2008)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Tellurides from Sunrise Dam gold deposit, Yilgarn Craton, Western Australia: a new occurrence of nagyágite - Y.-H. Sung; C. L. Ciobanu; A. Pring; J. Brügger; W. Skinner; N. J. Cook; M. Nugus (Mineralogy and Petrology, 2007)

Soil–water and solute movement under precision irrigation: knowledge gaps for managing sustainable root zones - S. R. Raine; W. S. Meyer; D. W. Rassam; J. L. Hutson; F. J. Cook (Irrigation Science, 2007)

Tree-ring reconstructed megadroughts over North America since a.d. 1300 - David W. Stahle; Falko K. Fye; Edward R. Cook; R. Daniel Griffin (Climatic Change, 2007)

Allelic and haplotypic diversity at the major histocompatibility class II within domesticated Australian Atlantic salmon ( Salmo salar L.) - J. W. Wynne; M. T. Cook; B. H. Holmes; N. G. Elliott (Journal of Fish Biology, 2007)
Variation within the major histocompatibility (MH) class II alpha gene ( Sasa‐DAA ) was compared between domesticated Australian Atlantic salmon and their ancestral Canadian population. The level of Sasa‐DAA and MH class II beta gene ( Sasa‐DAB ) sequence variation was also examined within the Australian population and compared with that published for European Atlantic salmon populations. In contrast to variation previously reported for non‐coding microsatellite loci, a high level of MH class II allelic variation has been maintained within the domesticated Australian populations. Furthermore, a high level of Sasa‐DAA and Sasa‐DAB allele sequence diversity was also observed and exceeded that reported for other cultured Atlantic salmon populations. The number of Sasa‐DAB allele sequences (14) surpassed the number of Sasa‐DAA allele sequences (9) to produce 14 unique class II haplotypes. We conclude that the Australian Atlantic salmon populations show high MH class II allelic and haplotypic variation compared with both its ancestral Canadian population and other cultured Atlantic salmon populations.

Liquid-feeding performances of ants (Formicidae): ecological and evolutionary implications - Diane W. Davidson; Steven C. Cook; Roy R. Snelling (Oecologia, 2005)

Liquid-feeding performances of ants (Formicidae): ecological and evolutionary implications - Diane W. Davidson; Steven C. Cook; Roy R. Snelling (Oecologia, 2004)

A collaborative model for research on decisional capacity and informed consent in older patients with schizophrenia: Bioethics unit of a geriatric psychiatry intervention research center - Dilip V. Jeste; Laura B. Dunn; Barton W. Palmer; Elyn Saks; Maureen Halpain; Alison Cook; Paul Appelbaum; Lawrence Schneiderman (Psychopharmacology, 2003)

The Use of Clinical Trial Simulation to Support Dose Selection: Application to Development of a New Treatment for Chronic Neuropathic Pain - Peter A. Lockwood; Jack A. Cook; Wayne E. Ewy; Jaap W. Mandema (Pharmaceutical Research, 2003)

Responses of the Aphids Phorodon humuli and Rhopalosiphum padi to Sex Pheromone Stereochemistry in the Field - Colin A. M. Campbell; Fraser J. Cook; John A. Pickett; Tom W. Pope; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 2003)

Inheritance of superoxide dismutase (Sod-1) in a perennial × annual ryegrass cross and its allelic distribution among cultivars - S. Warnke; R. Barker; L. Brilman; W. Young; R. Cook (Theoretical and Applied Genetics, 2002)

Post‐glacial colonization of northwestern North America by the forest‐associated American marten ( Martes americana , Mammalia: Carnivora: Mustelidae) - Karen D. Stone; Rodney W. Flynn; Joseph A. Cook (Molecular Ecology, 2002)
Phylogeographic patterns were used to assess intraspecific diversification of American martens ( Martes americana ). Within martens, two morphological groups ( americana and caurina ) have been recognized, though the level of distinction between them has been debated. We examined mitochondrial cytochrome b gene haplotypes from 680 martens to explore the colonization history of the Pacific Northwest and found two clades that correspond to the morphological groups. The widespread americana clade extends from interior Alaska south to Montana and eastward to Newfoundland and New England (i.e. northwestern, north‐central and northeastern North America). The caurina clade occurs in western North America, minimally extending from Admiralty Island (southeastern Alaska) south to Oregon and Wyoming. Our data indicated two colonization events for the Pacific Northwest (one by members of each clade) and were consistent with the persistence of populations throughout past glacial periods in eastern and western refugia. Due to vegetational and geological history following the past deglaciation, we hypothesize that martens of the caurina clade spread along the North Pacific Coast, and into southeastern Alaska, earlier than martens of the americana clade. Mismatch distributions for the americana clade were indicative of populations that recently experienced demographic expansion, while mismatch distributions for the caurina clade suggested that populations were at equilibrium. These clades are reciprocally monophyletic and distinctive (interclade divergence ranged from 2.5 to 3.0% (uncorrected p ), whereas, intraclade divergence was

Simulation of wind-driven circulation in the Salton Sea: implications for indigenous ecosystems - Christopher B. Cook; Gerald T. Orlob; David W. Huston (Hydrobiologia, 2002)

Using groundwater levels to estimate recharge - Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Choosing appropriate techniques for quantifying groundwater recharge - Bridget R. Scanlon; Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)
Location, Aim Long Island, 55 km north of New Guinea, erupted explosively in the seventeenth century and has been recolonized by animals and plants. Effectively in 1968, an island, Motmot, emerged from Long's 13 km‐diameter fresh‐water caldera lake, about 4 km from the nearest shore. A nested pair of colonization sequences is thus available for study. Long Island has been recolonized by birds, and Motmot has been colonized, presumably from the surrounding ring of Long Island. In order to monitor further colonization of Long Island following bird surveys in 1933 and 1972, and to survey the birds of Motmot, Motmot and the western parts of Long were visited for 15 days in 1999. Results In the last 66 years one species probably has become extinct; in the past 27 years three species have colonized and three, present in 1972, were not recorded in 1999. We assess the present number of nonmigrant land bird species as fifty. On Motmot, we recorded eight species, three breeding, and found two more only as prey remains (three raptor species were seen on the island). Main conclusions Long Island's avifauna still has youthful features. Species with good colonizing ability predominate, and there are no island‐endemic subspecies. There is a persistently high proportion of supertramps; none of the ten supertramps has been replaced by later‐colonizing ‘high‐S' species. A quasi‐equilibrium of about fifty species, fourteen fewer than the predicted equilibrium number for the island, has persisted for at least seven decades and may be seen as that appropriate to the present prolonged stage of Long's floral and vegetational development. Compared with the younger avifauna of Krakatau, Long's avifauna has a higher proportion of nectarivores, predators of large invertebrates and small vertebrates, and ground‐foraging insectivore‐herbivores, and a lower proportion of the insectivore‐frugivore guild. Motmot's small avifauna consists predominantly of species obtaining subsistence from outside the island.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. IV. Colonization by non‐avian vertebrates - S. Cook; R. Singidan; I. W. B. Thornton (Journal of Biogeography, 2001)
Aim In a 1999 expedition we surveyed the non‐avian vertebrates recolonizing a volcanic island off the north coast of Papua New Guinea, and the more recently emerged islet in its caldera lake. It is our intention with this research to document the reassembly of an ecosystem after a cataclysmic event at two temporal stages. Location Long Island, 55 km north of Papua New Guinea, erupted explosively in the seventeenth century. Its biota was destroyed and the island has been recolonized by animals and plants. From about 1953 to 1968, an island, Motmot, emerged from Long's freshwater caldera lake about 4 km from the nearest shore. Methods For 15 days in 1999 we surveyed the mammals, reptiles and amphibians of Motmot and the western parts of Long. Results We assess the present fauna as thirteen mammals, fourteen reptiles and two amphibians. Main conclusions Long appears to have a high proportion of tramp‐type species in its bat fauna, indicative of a developing biota. Several groups, especially snakes and amphibians, appear to be depauperate compared to the fauna of other islands in the area. On Motmot we recorded only one species of insectivorous bat; its vertebrate fauna is still in the very first stages of development.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. IV. Colonization by non-avian vertebrates - S. Cook; R. Singidan; I. W. B. Thornton (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)

The effects of feeding or addition of dissolved inorganic nutrients in maintaining the symbiosis between dinoflagellates and a tropical marine cnidarian - Fitt W.; Cook C. (Marine Biology, 2001)

Stability in the historical pattern of genetic structure of Newfoundland cod (Gadus morhua) despite the catastrophic decline in population size from 1964 to 1994 - Daniel E. Ruzzante; Christopher T. Taggart; Roger W. Doyle; Doug Cook (Conservation Genetics, 2001)

Estimating uncertainty in fish stock assessment and forecasting - Kenneth Patterson; Robin Cook; Chris Darby; Stratis Gavaris; Laurence Kell; Peter Lewy; Benoît Mesnil; André Punt; Victor Restrepo; Dankert W. Skagen; Gunnar Stefánsson (Fish and Fisheries, 2001)
A variety of tools are available to quantify uncertainty in age‐structured fish stock assessments and in management forecasts. These tools are based on particular choices for the underlying population dynamics model, the aspects of the assessment considered uncertain, and the approach for assessing uncertainty (Bayes, frequentist or likelihood). The current state of the art is advancing rapidly as a consequence of the availability of increased computational power, but there remains little consistency in the choices made for assessments and forecasts. This can be explained by several factors including the specifics of the species under consideration, the purpose for which the analysis is conducted and the institutional framework within which the methods are developed and used, including the availability and customary usage of software tools. Little testing of either the methods or their assumptions has yet been done. Thus, it is not possible to argue either that the methods perform well or perform poorly or that any particular conditioning choices are more appropriate in general terms than others. Despite much recent progress, fisheries science has yet to identify a means for identifying appropriate conditioning choices such that the probability distributions which are calculated for management purposes do adequately represent the probabilities of eventual real outcomes. Therefore, we conclude that increased focus should be placed on testing and carefully examining the choices made when conducting these analyses, and that more attention must be given to examining the sensitivity to alternative assumptions and model structures. Provision of advice concerning uncertainty in stock assessments should include consideration of such sensitivities, and should use model‐averaging methods, decision tables or management procedure simulations in cases where advice is strongly sensitive to model assumptions.

Sucrose transport by the alkaliphilic, thermophilic Bacillus sp. strain TA2.A1 is dependent on a sodium gradient - C. J. Peddie; Gregory M. Cook; Hugh W. Morgan (Extremophiles, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Identification of three genes expressed primarily during development in Physarum polycephalum - J. Bailey; L. J. Cook; R. Kilmer-Barber; E. Swanson; L. Solnica-Krezel; K. Lohman; W. F. Dove; J. Dee; R. W. Anderson (Archives of Microbiology, 1999)

The influence of nematodes on below-ground processes in grassland ecosystems - Richard D. Bardgett; Roger Cook; Gregor W. Yeates; Crystal S. Denton (Plant and Soil, 1999)

Construction of a bacterial artificial chromosome library of Medicago truncatula and identification of clones containing ethylene-response genes - Y.-W. Nam; R. V. Penmetsa; G. Endre; P. Uribe; D. Kim; D. R. Cook (Theoretical and Applied Genetics, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Evidence of deep circulation in two perennially ice‐covered Antarctic lakes - Scott W. Tyler; Peter G. Cook; Anya Z. Butt; James M. Thomas; Peter T. Doran; W. Berry Lyons (Limnology and Oceanography, 1998)
The perennial ice covers found on many of the lakes in the McMurdo Dry Valley region of the Antarctic have been postulated to severely limit mixing and convective turnover of these unique lakes. In this work, we utilize chlorofluorocarbon (CFC) concentration profiles from Lakes Hoare and Fryxell in the McMurdo Dry Valley to determine the extent of deep vertical mixing occurring over the last 50 years. Near the ice‐water interface, CFC concentrations in both lakes were well above saturation, in accordance with atmospheric gas supersaturations resulting from freezing under the perennial ice covers. Evidence of mixing throughout the water column at Lake Hoare was confirmed by the presence of CFCs throughout the water column and suggests vertical mixing times of 20–30 years. In Lake Fryxell, CFC‐11, CFC‐12, and CFC‐113 were found in the upper water column; however, degradation of CFC‐ 11 and CFC‐ 12 in the anoxic bottom waters appears to be occurring with CFC‐ 113 only present in these bottom waters. The presence of CFC‐113 in the bottom waters, in conjunction with previous work detecting tritium in these waters, strongly argues for the presence of convective mixing in Lake Fryxell. The evidence for deep mixing in these lakes may be an important, yet overlooked, phenomenon in the limnology of perennially icecovered lakes.

Axon guidance and somites - David Tannahill; Geoff M. W. Cook; Roger J. Keynes (Cell and Tissue Research, 1998)

Physiological changes in extracellular sodium directly control human proximal tubule growth and transport - David W. Johnson; Heather J. Saunders; Philip Poronnik; David I. Cook; Michael J. Field; Carol A. Pollock (Pflügers Archiv - European Journal of Physiology, 1997)

Axon guidance and somites - David Tannahill; Geoff M. W. Cook; Roger J. Keynes (Cell and Tissue Research, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

Does the uniform packing of sand in a cylinder provide a uniform penetration resistance? - Amanda Cook; C.A. Marriott; W. Seel; C.E. Mullins (Plant and Soil, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Limb regeneration and subsequent asymmetry in a male secondary sexual character influences sexual selection in wolf spiders - G. W. Uetz; William J. McClintock; Douglas Miller; Elizabeth I. Smith; Kristina K. Cook (Behavioral Ecology and Sociobiology, 1996)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Respiratory nitrate reduction by Desulfovibrio sp. - R. G. L. McCready; W. D. Gould; F. D. Cook (Archives of Microbiology, 1983)

Residues and dissipation of 2,4-D and 2,4-DCP in potato tubers - D. W. Bristol; D. C. Nelson; L. W. Cook (American Journal of Potato Research, 1981)

Taxonomic studies on strains of avian infectious bronchitis virus using neutralisation tests in tracheal organ cultures - J. H. Darbyshire; J. G. Rowell; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1979)

Growth comparisons of avian infectious bronchitis virus strains in organ cultures of chicken tissues - J. H. Darbyshire; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1978)

The use of chicken tracheal organ cultures for the isolation and assay of avian infectious bronchitis virus - Jane K. A. Cook; J. H. Darbyshire; R. W. Peters (Archives of Virology, 1976)

A potato breeding technique used for Texas - Bruce A. Perry; Robert V. Akeley; W. B. Cook (American Journal of Potato Research, 1960)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)

Sectional notes - Frank E. Garrett; Roy M. Barnes; W. Frank McGee; A. H. Eddins; W. B. Ward; Verne C. Beverly; H. A. Reiley; Allan W. Purdy; J. C. Campbell; H. J. Evans; Harold Mattson; O. D. Burke; et al. (American Journal of Potato Research, 1947)